Zinc Supplementation in Malnourished Children Under 5 Years with Acute Diarrhea - Iftikhar Ahmed , Awais Tahir ,Faisal Raza Malik (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate the effectiveness of zinc supplementation in malnourished children from 2 months to 5 years of age presenting with acute diarrhoea . Methods: In this case control study, malnourished children, with acute diarrhoea from 2 months to 5 years of age, were divided into two groups. Group 1 receiving oral zinc (10 mg/day for children <6 months and 20 mg/day for > 6 months ) and Group 2 children not receiving zinc(control group). Results: Total of 72 cases were enrolled in the study, out of which 45 (62%) children were male and 27 (38%) were female and 72 patients were in control group. Statistically significant differences were found in the duration of diarrhoea improvement (pvalue = 0.03), frequency of stools in 24 hours after the enrolment (p-value = 0.001) and stool volume (pvalue = 0.06) between children in oral zinc supplementation group and controls. Conclusion: The duration of diarrhoea improvement, frequency of diarrhoeal episodes and stool volume decrease significantly with oral zinc supplementation as compared to no zinc supplementation among malnourished children with acute diarrhoea.